The first grammar of (Kahenda-Mbaka) Kimbundu (Lisbon 1697) by Pedro Dias, S.J. (1621/1622–1700) and the ars minor (Lisbon 1573) by Manuel Álvares, S.J. (1526–1583) - Fernandes, Gonçalo (2021)
Pedro Dias, S.J. (1621/1622-1700) published the first known grammar book of (Kahenda-Mbaka) Kimbundu, entitled Arte da Lingua de Angola, oeferecida (sic) a Virgem Senhora N[ossa] do Rosario, Mãy, e Senhora dos mesmos Pretos (Lisboa 1697) [Grammar of the Language of Angola, offered to our Virgin Mother of the Rosary, and Lady of the Negroes] for use by the Jesuit missionaries, particularly in the north-eastern of Brazil, to instruct and convert the several Angolan and other Bantu western African slaves living there. Dias’ Arte, although a small book (only 48 pages) with no theoretical explanation, is a pioneering Bantu linguistic work, being the first known systematic grammar of Kimbundu whose Kahenda- Mbaka subdialect might be used as general or lingua franca in Bahia and Rio de Janeiro, Brazil, in the 17th century, and the second printed grammar of any Bantu language, preceded only by the Regulae quaedam pro difficillimi Congensium idiomatis faciliori captu ad grammaticae normam (Rome 1659) [Some rules to better understand the most difficult language of the Congo people, using the norm of the grammar] by Giacinto Brugiotti a Vetralla, O.F.M.Cap. The Arte da Lingua de Angola, in addition to the influence of the catechism (1642) by Francesco Pacconio, S.J. (1589–1641) and António do Couto, S.J. (1614–1666), is based on the ars minor (Lisboa 1573) by Manuel Álvares, S.J. (1526–1583).